A Study on Existing WATSAN Condition of Two Tea Gardens in - Chowdhury, MAI; Hasan, GMJ; Karim, MA (Journal of Environmental Science and Natural Resources, 2012)
In Bangladesh, the area around Sylhet is a traditional tea growing zone. Sylhet is not only plays an important role in the socio-economic development of Bangladesh but also important for ecological balance of the country. However, the water supply and sanitation (WATSAN) condition of tea garden area especially for workers is not environmentally sound. Moreover, there is not enough number of tube wells to get water for drinking purposes and even no provision of municipal water supply. The income of tea garden workers is poor around BDT 3000-4000 per month; 80% people were illiterate, 58% people were getting improper (shared among many workers) latrine facility. The drinking water was observed free from faecal coliform and arsenic contamination but the concentration of iron was high. This study reveals that both the tea garden people are deprived from proper latrine facility, water supply system, waste management and housing facilities. Sustainability of water supply and sanitation system must be considered for achieving good health for all and keep the environment healthy for smooth economic development. DOI: http://dx.doi.org/10.3329/jesnr.v4i2.10125 J. Environ. Sci. & Natural Resources, 4(2): 13-18, 2011